Problematic issues of Criminal and Criminal Procedural Legislation in Applying Coercive Medical Measures - D. V. Turenko (Bulletin of Kharkiv National University of Internal Affairs)
The author of the article proves that the possibility for a court to apply coercive medical measures to an insane person who has committed a socially dangerous act is regulated by the norms of the law on criminal liability and the provisions of the criminal procedural legislation of Ukraine. Their implementation is carried out in the interaction of substantive and procedural law, in particular in certain forms of criminal liability and in measures that are not covered by criminal liability, but are called criminal coercion, and is resolved through individual procedural institutions. The scientific positions of certain scholars and representatives of scientific schools on these issues were studied. On their basis the author expressed a number of own conclusions on problematic and debatable areas and issues raised in the article. Based on the results, the author of the article made some conclusions about the application of coercive medical measures: establishing the fact of committing a criminal offense by a specific person; after a forensic psychiatric examination to determine that such a person is mentally ill and according to its results cannot be sane; such a person is socially dangerous to society and must be isolated for the period of involuntary treatment. In the absence of at least one of the elements of the specified structure, coercive medical measures cannot be applied. The author made generalization, based on the initial provision that the main component of criminal liability is the conviction of a person, the adoption of a court conviction, which provides a legal assessment of the act and the specific person who committed it. Comparison of the current criminal and criminal procedural legislation provides an opportunity to assess coercive medical measures by coercive measures of a criminal law nature, as those used in criminal law relations against persons who committed a socially dangerous act, are ill with certain types of mental illness at the moment of the commission of a crime. The tendency of modern development of the direction in criminal law about delimitation of concepts and essence of "release of the person from criminal liability" and "punishment" from "exclusion of such responsibility" and existence and allocation at the same time of other direction - "criminal coercion" is distinguished. At the same time, the conclusions concerning persons who fell ill with a mental illness after the commission of a crime or while serving a sentence in places of imprisonment that relate to the procedural mechanism of temporary suspension of the imposed criminal punishment, were singled out. The results of the study of criminal and criminal procedural legislation on the application of coercive medical measures confirm and present the mechanism of interaction and implementation of substantive and procedural legislation to ensure the objectives of criminal proceedings under the Art. 1 of the Criminal Code and the Art. 2 of the Criminal Procedural Code of Ukraine.